ESTUDIO DE FACTIBLIDAD PARA LA CREACIÓN DE UNA CAJA DE AHORRO EN EL GOBIERNO AUTÓNOMO DESCENTRALIZADO MUNICIPAL DEL CANTÓN PALTAS - Ortega Sánchez, Michelle Carolina (2019)
The project "STUDY OF FEASIBILITY FOR THE CREATION OF A SAVING BOX IN THE DECENTRALIZED AUTONOMOUS GOVERNMENT OF CANTON PALTAS", aims to promote a culture of savings for each one of the employees and workers of the institution, and also to facilitate financing through credits, in order to improve the socio - economic development and the quality of life of each one of them. Therefore, the following inductive, deductive and analytical methods were used; and techniques such as: observation, bibliographical collection, and the survey that was addressed to the 242 employees and workers of the Municipal Autonomous Decentralized Government of the Paltas Canton. Allowing the development of the MARKET STUDY in which the main factors that affect the product such as demand and supply are defined; continuing, the TECHNICAL STUDY was carried out, where the size of the project was determined, which is the volume of the financial products that will be offered, the installed capacity, the same one that allows knowing the amount available for credit placements, and the volume of savings; the location, engineering, size and description of the equipment that was used was established, in the same way, flow charts were executed in order to take into account the processes to carry out the different activities within the savings bank. ADMINISTRATIVE STUDY - LEGAL, which aims to publicize the process of constitution of the entity, also exposes the current Legal Statute of the Superintendence of Popular and Solidarity Economy. Finally, the FINANCIAL STUDY was carried out, where the corresponding calculations are specified to determine if the project is feasible or not. Therefore, the techniques developed in the financial evaluation yielded the following results: a positive Net Present Value of 16.484,05, this being greater than zero; the Internal Rate of Return of 99,7%% that is higher than what the partners expect to obtain, the Period of Recovery of Capital of the investment is rescued in the two year and the Profit Cost Ratio of 1.06, is say that for every dollar invested a profit of 0.06 cents will be obtained, which means that the project for the creation of a savings bank in the GAD Paltas is feasible.